Evaluating Solid Medical Waste Management through SOP Compliance in HNGV Hospital Timor-Leste - Ivo Da Costa Soares; Rima Semiarty (Sakura Digital Nusantara, 2026)
Solid medical waste management in hospitals is essential for protecting public health and ensuring environmental safety, as improper handling of infectious and hazardous waste can lead to disease transmission and environmental contamination. As the national referral hospital in Timor-Leste, Hospital Nacional Guido Valadares (HNGV) has a critical responsibility to comply with established Standard Operating Procedures (SOPs) and national regulations. This study aimed to evaluate the level of compliance with SOPs in solid medical waste management at HNGV across four dimensions: policy, human resources, technical aspects, and operational processes, including containment, segregation, transportation, and disposal. A quantitative descriptive design with a survey approach was employed. Data were collected from cleaning staff and sanitation officers 60 using structured questionnaires and analyzed using descriptive statistical techniques, particularly percentage distribution, to measure SOP compliance levels. The results indicate a high level of compliance in several key indicators, including waste segregation (>90%), use of autoclave and incinerator systems (approximately 90–95%), and adherence to personal protective equipment (PPE) protocols (>90%). However, lower compliance was observed in temporary waste storage adequacy (<80%) and consistent use of specific protective equipment. Overall, HNGV’s solid medical waste management system generally meets established standards, although gaps remain in infrastructure and operational consistency. This study contributes to the existing literature by providing empirical evidence on SOP-based compliance in hospital waste management within a developing country context and highlights the need for strengthening infrastructure, equipment provision, and continuous monitoring systems to enhance sustainable medical waste management practices.